Basilisks and Beowulf : monsters in the Anglo-Saxon world - Flight, Tim, 1987- (Reaktion Books, Limited, 2021)
An eye-opening, engrossing look at the central role of monsters in the Anglo-Saxon worldview--now in paperback.This book addresses a simple question: why were the Anglo-Saxons obsessed with monsters, many of which did not exist? Drawing on literature and art, theology, and a wealth of firsthand evidence, Basilisks and Beowulf reveals a people huddled at the edge of the known map, using the fantastic and the grotesque as a way of understanding the world around them and their place within it. For the Anglo-Saxons, monsters helped to distinguish the sacred and the profane; they carried God's message to mankind, exposing His divine hand in creation itself. At the same time, monsters were agents of disorder, seeking to kill people, conquer their lands, and even challenge what it meant to be human. Learning about where monsters lived and how they behaved allowed the Anglo-Saxons to situate themselves in the world, as well as to apprehend something of the divine plan. It is for these reasons that monsters were at the very center of their worldview. From map monsters to demons, dragons to Leviathan, we neglect these beasts at our peril.